2018
DOI: 10.1038/s41395-018-0393-0
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Other Risk Factors in Individuals With Synchronous Conventional High-Risk Adenomas and Clinically Significant Serrated Polyps

Abstract: Serrated polyps (SPs) are an important focus of colorectal cancer (CRC) screening, accounting for up to 30% of all CRCs [1]. Over the last decade, there has been an increasing awareness about lesions in the serrated pathway. These lesions may be detected in a large proportion of screening exams [2]. SPs represent a heterogeneous group of polyps that includes sessile serrated adeno-mas/polyps (SSA/P), traditional serrated adenomas (TSA), and hyperplastic polyps (HP). [1, 3-7] While diminutive HPs are believed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…After being inhaled, nicotine crosses the alveolar surface of the lungs, stimulating ß-adrenoceptors and generating elevated levels of cyclooxygenase-2 (COX-2), prostaglandin-E2 and vascular endothelial growth factor (VEGF), favoring the nicotine exchange in the smoker's tissues; these findings provide an association of nicotine with the genesis of lesions, cellular modifications and even cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…After being inhaled, nicotine crosses the alveolar surface of the lungs, stimulating ß-adrenoceptors and generating elevated levels of cyclooxygenase-2 (COX-2), prostaglandin-E2 and vascular endothelial growth factor (VEGF), favoring the nicotine exchange in the smoker's tissues; these findings provide an association of nicotine with the genesis of lesions, cellular modifications and even cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…With time, progression of dysplasia leads to a well-known adenoma-carcinoma sequence. Various risk factors have been associated with high-grade dysplasia adenoma, including genetic predisposition, inflammatory bowel diseases, age, male sex, smoking, poor dietary habits, obesity and metabolic syndrome[ 18 , 19 ]. Since metabolic syndrome is experiencing a worldwide epidemic-like rise in incidence, its clinical consequences such as tumors, with colorectal adenomas and carcinomas among others, are also experiencing a dramatic rise[ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 One study has shown that these individuals with both types of polyps may have a unique risk profile. 24 Specifically, those with both serrated polyps and conventional adenomas have an association with smoking that is stronger than those with either type of polyp only. Unfortunately, a risk profile analysis with the 69 individuals with both serrated and conventional adenomas was not performed in the current analysis.…”
mentioning
confidence: 96%